ADRENAL INCIDENTALOMA: THE CLUES TO AID DIAGNOSIS - Nordin, Noor Fareha binti (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Adrenal incidentaloma (AI) is found while imaging for a different purpose when there are no overt signs of adrenal illness. A thorough history and examination of a patient with adrenal insufficiency may provide more hints to help diagnose and narrow the differentials. CASE The first patient is a 25-year-old male with hypertension and chronic diarrhoea. Blood investigation showed deranged liver function. Ultrasound of the abdomen revealed a heterogenous hyperechoic mass at the right suprarenal region measuring 6.9 x 5.8 x 7.5 cm (APxWxCC) which is compressing the adjacent right liver lobe. Twenty-four-hour urinary-free metanephrine demonstrated that metanephrine and normetanephrine levels were twenty times higher than the upper limit of the reference value. For the second patient, a 49-year-old female with hypertension and asthma presented with acute asthma exacerbation at the ED and POCUS showed an incidental finding of a right liver mass. Ultrasound of the abdomen showed a well-defined, heterogeneous hypoechoic, mixed solid-cystic lesion superior to the right kidney measuring 8.0 x 7.3 x 9.4 cm, suggestive of a right adrenal mass. Twentyfour-hour urinary-free metanephrine showed elevated normetanephrine 37.40 umol/24H (0.88-2.88). The third patient is a 49-year-old female who presented with abdominal discomfort, anorexia and weight loss of 3 kg over 3-4 months. Colonoscopy and OGDS yielded normal results. Ultrasound of the abdomen showed a large, heterogeneous lobulated lesion seen in the left retroperitoneal region measuring 11.9 x 5.4 x 6.2 cm. Twenty-four-hour urine-free metanephrine was normal. Corticoadrenal carcinoma was ruled out. Serial CT of the adrenal done two months apart showed a rapid increase in the size of the left adrenal mass with multiple enlarged lymph nodes. CT-guided biopsy of the left adrenal revealed primary diffuse large B cell lymphoma. CONCLUSION Hypertension is common in patients with adrenal insufficiency. Symptoms and blood investigation can give clues to the specific adrenal hyperfunction present which can help narrow down the differentials, thus reducing the cost of work-up in a resource limited centre. A patient with phaeochromocytoma might be asymptomatic and a low level of urine metanephrine could be due to a necrotic tumour. Computed tomography of the adrenal is essential to assess the characteristics of the lesion to further risk stratify the patient.